The Young Platelet Population in Children with Cyanotic Congenital Heart Disease - Goldschmidt, Béla; Sørland, Svein Jan (Thrombosis and Haemostasis, 1976)
Some morphological, biochemical and functional parameters of platelet population in children with cyanotic congenital heart disease (CCHD) were studied by making comparisons of the normal platelet population in both CCHD patients and controls. The mean volume of the platelets from cyanotic patients was greater than from normals. The platelet size distribution curves demonstrated a shift towards larger than normal size in the case of CCHD. The mean protein content, as well as the mean PF3 content of platelets was increased in CCHD. Following addition of kaolin, PF3 release was more rapid and of shorter duration with platelets from CCHD patients as compared to normal platelets. They also released more PF3 than did normal platelets. After addition of ADP, collagen, or adrenalin, platelets of CCHD patients were more responsive than similarly treated platelets from normals. Platelets from CCHD showed an increased initial rate of aggregation and greater maximum aggregation. These data suggested that the platelet population of CCHD patients consists of larger, younger and functionally more active platelets than does the platelet population of normals.